2011
DOI: 10.1128/aem.05035-11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacillus thuringiensis l -Isoleucine Dioxygenase for Production of Useful Amino Acids

Abstract: We determined the enzymatic characteristics of an industrially important biocatalyst, ␣-ketoglutaratedependent L-isoleucine dioxygenase (IDO), which was found to be the enzyme responsible for the generation of (2S,3R,4S)-4-hydroxyisoleucine in Bacillus thuringiensis 2e2. Depending on the amino acid used as the substrate, IDO catalyzed three different types of oxidation reactions: hydroxylation, dehydrogenation, and sulfoxidation. IDO stereoselectively hydroxylated several hydrophobic aliphatic L-amino acids, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 38 publications
8
61
0
Order By: Relevance
“…2a,b). Preliminary TLC and HPLC analyses demonstrated that the L-isoleucine, L-leucine hydroxylation and L-methionine oxidation products were the same as those synthesized by IDO and previously characterized by us (Hibi et al, 2011). 2c).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…2a,b). Preliminary TLC and HPLC analyses demonstrated that the L-isoleucine, L-leucine hydroxylation and L-methionine oxidation products were the same as those synthesized by IDO and previously characterized by us (Hibi et al, 2011). 2c).…”
Section: Resultssupporting
confidence: 61%
“…The hydroxylated L-Thr was collected, eluted with water, freeze-dried and analysed by ESI-MS as described in (Hibi et al, 2011). Subsequently, IPTG was added to a final concentration of 1 mM, and the culture was incubated for an additional 2 h. The biomass was harvested by centrifugation and re-suspended in 5 mL of 50 mM HEPES (pH 7) and lysed by one pass through a French press (1000 psi).…”
Section: Preparation and Identification Of Hydroxylated L-threoninementioning
confidence: 99%
“…Moreover, the addition of ferrous iron, ␣KG, and ascorbate to the reaction mixture was required for the maximum activity of the F. oxysporum c8D cell lysate. Since similar observations have been made for other amino acid hydroxylases belonging to the Fe/␣KG-DO superfamily (19)(20)(21), these results suggest that the enzyme responsible for L-Pip-hydroxylating activity belongs to the Fe/␣KG-DO superfamily.…”
Section: Resultssupporting
confidence: 57%
“…Some hydroxy amino acids can also be used as precursors in the asymmetric synthesis of pharmaceuticals [1]. For example, (2 S, 3 R, 4 S )-4-hydroxyisoleucine has insulinotropic and anti-obesity effects and seems to have potential for the treatment of diabetes [2].…”
Section: Introductionmentioning
confidence: 99%